2009
DOI: 10.1007/s00128-009-9894-2
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Induction of Sperm Head Abnormalities in Mice, Mus musculus, Exposed to Radiofrequency Radiations from Global System for Mobile Communication Base Stations

Abstract: The exposure of male mice to radiofrequency radiations from mobile phone (GSM) base stations at a workplace complex and residential quarters caused 39.78 and 46.03%, respectively, in sperm head abnormalities compared to 2.13% in control group. Statistical analysis of sperm head abnormality score showed that there was a significant (p < 0.05) difference in occurrence of sperm head abnormalities in test animals. The major abnormalities observed were knobbed hook, pin-head and banana-shaped sperm head. The occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…Male mice exposed to RF-EMR from mobile phone base stations at a workplace complex and residential quarters had significantly and in dose-dependent manner more sperm head abnormalities (knobbed hook, pin-head and bananashaped sperm head) compared to unexposed animals (40% versus 2%, respectively) [7]. The study implicated that living in close proximity to mobile base stations might have an adverse outcome on male reproductive health [7].…”
Section: Studies In Malesmentioning
confidence: 90%
See 2 more Smart Citations
“…Male mice exposed to RF-EMR from mobile phone base stations at a workplace complex and residential quarters had significantly and in dose-dependent manner more sperm head abnormalities (knobbed hook, pin-head and bananashaped sperm head) compared to unexposed animals (40% versus 2%, respectively) [7]. The study implicated that living in close proximity to mobile base stations might have an adverse outcome on male reproductive health [7].…”
Section: Studies In Malesmentioning
confidence: 90%
“…A number of recent reports have suggested a possible link between cell phone use and male infertility [4][5][6][7][8][9][10][11][12]. The concern has arisen that carrying a cellular phone near the reproductive organs such as the testes may cause dysfunction and particularly a decrease in sperm development and production, and thus decrease fertility in men.…”
Section: Studies In Malesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bruce and Heddle (63) attributed the occurrence of sperm head abnormalities to the chromosomal aberrations that occur during the packaging of genetic material in the sperm head or occurrence of point mutation in testicular DNA. Several studies (64)(65)(66)(67) reported that abnormalities may also arise as a consequence of mistakes in the spermatozoa-differentiating process during spermatogenesis. Another two studies (66,67) reported that abnormalities in sperm heads may occur by physiological, cytotoxic or genetic mechanisms or alterations in testicular DNA which in turn disrupts the process of differentiation of spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Each group was placed in the exposure cages located below the GSM base stations at a distance of 1-50m from the base. Total exposures due to radiofrequency field strength from mobile phone base station 1, station 2 and control station, were measured with the aid of a wide spectrum Aeritalia Radiofrequency Field Strength measuring meter at distances of 0, 50, 100, 150, 200, 250 and 300m as previously described (Otitoloju et al, 2010).…”
Section: Measurement Of Radiofrequency Radiation From Gsm Base Stationsmentioning
confidence: 99%